Production Networks and Enterprises in East Asia Industry and Firm-level Analysis - Wignaraja, Ganeshan; SpringerLink (Online service) (Tokyo : Springer Japan : Imprint: Springer, 2016)
The book provides a comprehensive examination of patterns and determinants of production networks in East Asia, a key driver in the region s global success. It provides the reader with an accessible understanding of the theoretical literature on production networks and recent developments in empirical analysis at the industry and firm-levels. The topics covered in the book include gross trade in parts and components and gravity models, trade in value added, industry case studies, and microdata econometric studies of firm heterogeneity in production networks. The microdata econometric studies explore key aspects of the heterogeneity of firms in East Asian production networks such as technological capability, the entry of small and medium-sized enterprises into production networks, business use of free trade agreements, and access to credit. Blending new sources of data, empirical tools, and econometric methods, this book is highly recommended for readers who seek to understand the workings of the complex web of production networks in East Asia. Ganeshan Wignaraja is advisor in the Economic Research and Regional Cooperation Department of the Asian Development Bank. Previously he was director of research of the Asian Development Bank Institute. He has a doctorate in economics from the University of Oxford and has published 15 books on international economics, regional integration, and economic development. .
Part 1 Introduction and Overview -- 1 Introduction (Ganeshan Wignaraja) -- 2 Toward Trade Policy Analysis 2.0: From National Comparative Advantage to Firm-Level Trade Data (Lucian Cernat) -- 3 Production Networks in East Asia: What We Know So Far (Fukunari Kimura and Ayako Obashi) -- Part 2 Industry Analysis in East Asia -- 4 The Changing Nature of the Production Network in East Asia (Matthias Helble and Boon-Loong Ngiang) -- 5 Exports of Parts and Components by Different Types of Firms in the People s Republic of China: A Comprehensive Examination (Hyun-Hoon Lee, Donghyun Park, and Jing Wang) -- 6 The Evolution of Industrial Networks in East Asia: Stylized Facts and Role of Trade Facilitation Policies (Hubert Escaith and Satoshi Inomata) -- 7 Production Networks in Asia: A Case Study from the Hard Disc Drive Industry (Daisuke Hiratsuka) -- Part 3 Firm-Level Analysis in East Asia -- 8 Production Networks, Profits, and Innovative Activity: Evidence from Malaysia and Thailand (Ganeshan Wignaraja, Jens Krüger, and Anna-Mae Tuazon) -- 9 Understanding Innovation in Production Networks in Firms in the People s Republic of China, Thailand, and the Philippines (Ganeshan Wignaraja) -- 10 SME Internationalization through Global Value Chains and Free Trade Agreements: Evidence from Malaysia (Menaka Arudchelvan and Ganeshan Wignaraja) -- 11 SME Finance and Trade at the Firm-Level: Evidence from the People s Republic of China and ASEAN Economies (Yothin Jinjarak, Paulo Jose Mutuc, and Ganeshan Wignaraja) -- Part 4 Beyond East Asia -- 12 Global Value Chains and Least Developed Countries in Asia: Cost and Capability Considerations in Cambodia and Nepal (Jodie Keane and Yurendra Basnett) -- 13 Donor Support for Connecting Firms in Asia to Value Chains (William Hynes and Frans Lammersen).
Keywords: Trade; Business; Commerce; Microeconomics; Industrial organization; International economics; Economics; International Economics; Microeconomics; Industrial Organization; Trade; Electronic books